Блиссимволика как способ общения детей с ДЦП - Жусупова, И.Т. (My University, 2013)
In the structure of children`s disability are children's cerebral paralysis. Children with cerebral paralysis are experiencing huge difficulties in mastering their own speech. One of the ways to communicate such children is Blissymbols. Bliss is a semantic language system that can substitute for any other natural language. Instead of letters are used basic graphic symbols, that easy to remember even to the child. The purpose of the method-Bliss with disabled children is communication and language development of a child. Proper use of methods allows Bliss-communication to achieve positive results. The child overcomes the obstacles that standing in the way of its development, for example, eliminates the barrier of communication with other people, reveals the internal plan of its features, and also enhances the child's faith in its communicative possibilities, softened by a sense of inferiority.